Trade union engagements on the SDGs and union revitalization in five Asian countries - Melisa R. Serrano; Mary Leian Marasigan (International Labour Organization (ILO), 2024)
Trade unions play an important role in ensuring that the Sustainable Development Goals (SDGs) are integrated into the development agenda and strategies of countries. The findings from indepth online interviews with trade union officers from seven national labour confederations and senior ILO officials in five Asian countries, complemented by a review of secondary sources, show that, depending on a set of factors, trade unions utilize a variety of strategies in influencing their country's commitments to and progress on achieving the SDGs. The paper argues that both the strategies and outcomes of the SDG-related engagements of the unions in three of the five countries, which are influenced by several important factors, have contributed, albeit to varying degrees, to their revitalization in terms of the development and strengthening of their power resources, particularly the unions' institutional power. The paper identifies several ways that trade unions can sustain successful SDG-related initiatives.
Keywords: 330; Sustainable Development Goals; SDGs; trade unions; union revitalization; social dialogue